DINAMIKA EKONOMI-POLITIK ASEAN: Optimalisasi Kebijakan Kawasan Perdagangan Bebas - Khaldun, Riady Ibnu (Center for Integrative International Studies Laboratory, Faculty of Political and Social Sciences, UIN Sunan Ampel Surabaya, 2022)
Within few years since its establishment in 1967, ASEAN has ratified various economic policies to encourage the creation of welfare for member countries as stipulated in the ASEAN charter. One of them is the policy of implementing free trade with the aim of relaxing the flow of goods and services in the ASEAN region through a single market mechanism using the CEPT scheme. Since the establishment of ASEAN there have been various policies that have been ratified such as AFTA but their implementation has not been carried out optimally, especially in maximizing profits through these policies so it is necessary to improve related to the management of superior commodities and the development of competitiveness superior product.